2019
DOI: 10.1016/j.chemgeo.2019.07.032
|View full text |Cite
|
Sign up to set email alerts
|

First-principles modeling of chlorine isotope fractionation between chloride-bearing molecules and minerals

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 79 publications
1
9
1
Order By: Relevance
“…It is expected that the theoretical stretching frequencies obtained in the present study overestimate the frequencies experimentally observed at ambient temperature by typically 10 to 50 cm −1 , as observed in quartz (Jollands et al, 2020). A stronger overestimation, amounting to 125 cm −1 , has, however, been recently observed for OH defects in corundum (Balan, 2020). We will see in the following that the theoretical frequencies of OH defects in diopside are systematically upshifted by ∼ 50 cm −1 compared to their experimental counterparts (Fig.…”
Section: General Properties Of Oh-bearing Defects In Diopsidecontrasting
confidence: 49%
“…It is expected that the theoretical stretching frequencies obtained in the present study overestimate the frequencies experimentally observed at ambient temperature by typically 10 to 50 cm −1 , as observed in quartz (Jollands et al, 2020). A stronger overestimation, amounting to 125 cm −1 , has, however, been recently observed for OH defects in corundum (Balan, 2020). We will see in the following that the theoretical frequencies of OH defects in diopside are systematically upshifted by ∼ 50 cm −1 compared to their experimental counterparts (Fig.…”
Section: General Properties Of Oh-bearing Defects In Diopsidecontrasting
confidence: 49%
“…The substitution of boron or aluminum for silicon has been experimentally investigated and revealed a number of associated OH-stretching bands. Quartz samples grown in high-B systems display a characteristic band at 3596 cm −1 that has been ascribed to a (B,OH) defect (Staats and Kopp, 1974;Thomas et al, 2009;Baron et al, 2015). This band has a dominant polarization in the (001) plane and a weaker contribution parallel to the [001] direction (Thomas et al, 2009;Baron et al, 2015).…”
Section: Oh Defects Associated With Chemical Impuritiesmentioning
confidence: 99%
“…Quartz samples grown in high-B systems display a characteristic band at 3596 cm −1 that has been ascribed to a (B,OH) defect (Staats and Kopp, 1974;Thomas et al, 2009;Baron et al, 2015). This band has a dominant polarization in the (001) plane and a weaker contribution parallel to the [001] direction (Thomas et al, 2009;Baron et al, 2015). In the quartzalbite-water or granite-water systems, IR spectra of quartz display three bands polarized in the (001) plane and observed at 3313, 3379 and 3431 cm −1 (Stalder and Konzett, 2012).…”
Section: Oh Defects Associated With Chemical Impuritiesmentioning
confidence: 99%
See 2 more Smart Citations